1991
DOI: 10.2527/1991.6962434x
|View full text |Cite
|
Sign up to set email alerts
|

Heat balance characteristics of limit-fed growing pigs of several breeds kept in groups at and below thermal neutrality.

Abstract: The lower critical temperature (Tcr) and thermoregulatory heat production below Tcr were studied in Norwegian Landrace (N), Finnish Landrace (F), Dutch Landrace (D), and Great Yorkshire (Y) barrows. Animals, weighing 26 kg at the start, were kept in groups for 18, 2-d periods in climate respiration chambers at environmental temperatures (Tenv) between 11 and 26 degrees C. Feeding level of animals in a group was 93 g.kg-.75.d-1 (2.5 times maintenance) and based on mean BW. Great Yorkshire pigs had a higher grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…This assumption is reinforced by the lower RR value at 34 °C in CR than in LW pigs. According to Henken et al [14], the lower LCT measured in LW than in Landrace pigs was connected to an increase of backfat thickness. This increase of thermal insulation resulted in a decrease in the thermal heat transfer coefficient and the ability to lose heat [15].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This assumption is reinforced by the lower RR value at 34 °C in CR than in LW pigs. According to Henken et al [14], the lower LCT measured in LW than in Landrace pigs was connected to an increase of backfat thickness. This increase of thermal insulation resulted in a decrease in the thermal heat transfer coefficient and the ability to lose heat [15].…”
Section: Discussionmentioning
confidence: 96%
“…The reports on the effect of breed on the lower or upper limits of the thermal comfort zone in the pig and therefore, on its tolerance to heat stress, are scarce, in contrast to ruminant or poultry species. In pigs, the existence of a different heat tolerance among breeds is reported between halothane positive and negative boars [1,9,27] and between high and low producing genotypes [14,21]. In both of the latter studies, heat tolerance of low producing lines is attributed to their lower heat production as a consequence of their low productivity and maintenance requirements suggesting that low production is itself an adaptive attribute [2].…”
Section: Introductionmentioning
confidence: 99%
“…This makes it impossible to combine the findings into one correction formula. However, studies have shown that skin areas with an increased fat layer (non-thermal window), which may be breed dependent, have a lower regression constant and higher coefficient [ 30 ]. This means that skin temperature is lower at low ambient temperatures due to the fat insulation, while increasing ambient temperature rapidly increases the skin temperature, due to the vasocontrolled thermoregulation, supplying more blood to the skin tissue.…”
Section: Introductionmentioning
confidence: 99%
“…weight (kg) Surface area(s) Thermal Window (X: yes) T ambient [°C] Regression Constant, T 0 [°C] ( A ) Regression coefficient, b ( A ) Correlation (r) and goodness of fit (R 2 ) ( A ) Remarks Henken et al . [ 30 ] 16 Norwegian, Finnish and Dutch Landrace and Great Yorkshire 26 Lumbal area 11-26 22.5–25.9 0.37–0.47 r = 0.83–0.91 (**) ( B ) Wendt et al . [ 34 ] 89 7–60 Ear base X 12–30 28.5 0.263 r = −0.68 (***) ( C ) 147 160–222 27.6 Loughmiller et al .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, there is a relationship between surface temperature and ambient temperature. Thus, the accuracy of the body temperature value can be influenced by incidental contact with some areas of the skin from which hair may be growing, which can influence the accuracy of the measurement recorded by IRTM (Henken et al, 1991). Moreover, body temperature measurements obtained from pigs will be very useful if a system is established that can make on-site assessments and then remotely report to vets who are assisting in the monitoring of the potential for disease outbreaks on farms.…”
Section: Introductionmentioning
confidence: 99%